Adsorptive properties of silica gel for biodiesel refining - Mazzieri, Vanina Alejandra (2008)
The refining of biodiesel by adsorption over silica gel was assessed. Silica gel samples were used for the adsorption of glycerol and monoglycerides. Room-temperature isotherms for the adsorption of glycerol were measured for biodiesel samples contaning only fatty acid methyl esters or samples spiked with contaminants, such as water, methanol, monoglycerides, and soaps. The results indicate that adsorption of glycerol and monoglycerides contained in biodiesel over silica is very efficient and robust. Adsorption of glycerol is not influenced by the presence of small amounts of water arid soaps. The presence of monoglycerides lowers the adsorption capacity of glycerol because of the competition of monoglycerides for the same adsorption sites. Methanol adversely affects the adsorption in a different way. It increases the activity of glycerol in the liquid phase and reduces the adsorption affinity and adsorption capacity of silica. Conventional biodiesel refining downstream transesterification reactors currently performed by decanting/washing or centrifugation/washing can be conveniently replaced by simple decanting and silica adsorption, thus preventing the issue of excessive amount of effluent waters.